Desarrollo De Un Prototipo De Gafas Basado En Movimientos Oculares Sacádicos Provenientes De La Señal Electrooculografía (EOG) Para La Asistencia Digital De Personas Con Discapacidad Motriz Severa (2025)
Disability refers to a condition that can be attributed to a wide variety of factors, whether external or congenital in origin. Among these factors, traumatic injuries, infections, spinal cord diseases, and even complications resulting from medical procedures stand out. These conditions significantly affect the quality of life of those who experience them, limiting their autonomy and mobility. For this reason, the development of assistive technologies is essential to mitigate such limitations and contribute to improving the lives of people with disabilities. In this context, one of the most promising emerging technologies is the use of electrooculography (EOG)-based glasses, which enable the intuitive control of devices such as wheelchairs by tracking the user's eye movements. These glasses represent an innovative solution that promotes the independent mobility of people with motor disabilities, significantly enhancing their interaction with their surroundings. The main objective of this project is the design and development of a rehabilitation system based on EOG glasses. This system will not only capture and process the signals generated by eye movements but also adapt them for different applications in the field of rehabilitation. In doing so, it aims to provide a technological tool that facilitates mobility, improves quality of life, and promotes the inclusion of people with reduced mobility in their daily activities